Inhibitory Circuits in the Basolateral Amygdala in Aversive Learning and Memory - Perumal, Madhusoothanan B.; Sah, Pankaj (Frontiers in Neural Circuits, 2021)
Neural circuits in the basolateral amygdala (BLA) play a pivotal role in the learning and memory formation, and processing of emotionally salient experiences, particularly aversive ones. A diverse population of GABAergic neurons present in the BLA orchestrate local circuits to mediate emotional memory functions. Targeted manipulation of GABAergic neuronal subtypes has shed light on cell-type specific functional roles in the fear learning and memory, revealing organizing principles for the operation of inhibitory circuit motifs in the BLA.